Biotechnology of vegetable waste recycling using modern EM technologies - Kuskova, V.V.; Korniienko, I.M.; Garkava, K.G.; Monchenko, O.V.; Chernenko, Y.M.; Kuz , T.V. (Problems of Environmental Biotechnology, 2023)
The recycling of vegetable waste (carrot, potato and beet) using modern EM technologies is proposed as an urgent solution to the problem of waste processing and utilization.